Impaired Distal Perfusion Predicts Length of Hospital Stay in Patients with Symptomatic Middle Cerebral Artery Stenosis. Issue 3 (10th February 2021) - Yaghi, Shadi; Havenon, Adam de; Honda, Tristan; Hinman, Jason D.; Raychev, Radoslav; Sharma, Latisha K.; Kim, Song; Feldmann, Edward; Romano, Jose G.; Prabhakaran, Shyam; Liebeskind, David S.
ABSTRACT: BACKGROUND AND PURPOSE: Perfusion imaging can risk stratify patients with symptomatic intracranial stenosis. We aim to determine the association between perfusion delay and length of hospital stay (LOS) in symptomatic middle cerebral artery (MCA) stenosis patients. METHODS: This is a retrospective study of consecutive patients admitted to a comprehensive stroke center over 5 years with ischemic stroke or transient ischemic attack (TIA) within 7 days of symptom onset due to MCA stenosis (50‐99%) and underwent perfusion imaging. Patients were divided into three groups: mismatch volume ≥ 15 cc based on T max > 6 second delay, T max 4‐6 second delay, and <4 second delay. The outcome was LOS, both as a continuous variable and categorical (≥7 days [prolonged LOS] vs. <7 days). We used adjusted regression analyses to determine the association between perfusion categories and LOS. RESULTS: One hundred and seventy eight of 194 patients met the inclusion criteria. After adjusting for age and NIHSS, T max >6 second mismatch was associated with prolonged LOS (OR 2.94 95% CI 1.06‐8.18; P = .039), but T max 4‐6 second was not (OR 1.45 95% CI .46‐4.58, P = .528). We found similar associations when LOS was a continuous variable for T max > 6 second (β coefficient = 2.01, 95% CI .05‐3.97, P = .044) and T max 4‐6 second (β coefficient = 1.24, 95% CI –.85 to 3.34, P = .244). CONCLUSION: In patients with symptomatic MCA stenosis, T max > 6 second perfusion delay is associated with prolonged LOS. Prospective studies are needed to validate our findings.